Chemistry for engineering students - Brown, Lawrence S.; Thomas A. Holme (Belmont, California : Brooks/Cole Publishing Company, 2011)
Enhanced with a remarkable number of new problems and applications, the Second Edition of CHEMISTRY FOR ENGINEERING STUDENTS provides a concise, thorough, and relevant introduction to chemistry that prepares students for further study in any engineering field. Updated with even more questions and applications specifically geared toward engineering students, the book emphasizes the connection between molecular properties and observable physical properties and the connections between chemistry and other subjects studied by engineering students, such as mathematics and physics. This new edition is now fully supported by OWL, the most widely-used online learning system for chemistry.
Includes index 1. Introduction to Chemistry. 2. Atoms and Molecules. 3. Molecules, Moles, & Chemical Equations. 4. Stoichiometry. 5. Gases. 6. The Periodic Table and Atomic Structure. 7. Chemical Bonding and Molecular Structure. 8. Molecules and Materials. 9. Energy and Chemistry. 10. Entropy and the Second Law of Thermodynamics. 11. Chemical Kinetics. 12. Chemical Equilibrium. 13. Electrochemistry. 14. Nuclear Chemistry
Includes index.
Keywords: CHEMISTRY -- TEXTBOOKS